2005
DOI: 10.1007/s10620-005-2452-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cdx2 in Early GRCL of Barrett?s Esophagus Induced in Rats by Duodenal Reflux

Abstract: The intestine-specific caudal-related homeobox transcription factor Cdx2 is widely accepted to play a key role in intestinal development and differentiation in mammals. We studied the role of Cdx2 in the development of Barrett's esophagus (BE). In previous studies, we have shown a sequence of morphological changes of squamous epithelium leading to BE, found a peculiar metaplastic change common to other parts of gut, and proposed the concept of a "gut regenerative cell lineage" (GRCL). The GRCL is characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 29 publications
2
53
1
Order By: Relevance
“…Among them, anti-CDX2 antibody against human tissue is reported to react with rat CDX2, 8,9 and our preliminary study also confirmed that this antibody reacted with the nuclei of cell of the small intestinal epithelium of PCK rats. Therefore, we used this antibody in this study using rat specimens.…”
Section: Antibodies and Other Reagentssupporting
confidence: 78%
See 1 more Smart Citation
“…Among them, anti-CDX2 antibody against human tissue is reported to react with rat CDX2, 8,9 and our preliminary study also confirmed that this antibody reacted with the nuclei of cell of the small intestinal epithelium of PCK rats. Therefore, we used this antibody in this study using rat specimens.…”
Section: Antibodies and Other Reagentssupporting
confidence: 78%
“…2,4,5-8 CDX2-dependent intestinal metaplasia is noted in Barrett's esophagus with MUC2 expression, and bile acid and chronic acid exposure have been reported to induce CDX2 expression. 2,[4][5][6]8,9 Intestinal metaplasia is also involved in the pathogenesis of biliary diseases. For example, in chronic cholangitis such as hepatolithiasis, intestinal metaplasia with goblet cells occurs, and MUC2 is aberrantly expressed in goblet cells colocalized with CDX2.…”
mentioning
confidence: 99%
“…This is an adaptive response to protect the epithelium, since metaplastic tissue is more resistant to change than natural tissue. Recent studies determined that the metaplastic changes are driven by increased expression of the homeobox genes related with intestinal development (Cdx2) [12]. These genes are activated by bile acids such as deoxycholic acid and cholic acids [13,14].…”
Section: Inflammation-metaplasia-adenocarcinoma Sequence In a Rat Modelmentioning
confidence: 99%
“…The role of bile reflux has been established from surgical models in rats, where esophagojejunostomy and esophagogastroduodenostomy results in a mixed bile and gastric refluxate that leads to intestinal metaplasia, with many similarities to human BE, including early induction of Cdx1 and Cdx2 expression and the development of a columnar-lined epithelium containing intestinal mucin-secreting goblet cells, [21][22][23][24][25] and esophageal adenocarcinoma. 26,27 Bile acids, particularly unconjugated bile acids such as deoxycholate that induce DNA damage, are one component of gastroduodenal reflux that has been strongly linked to the development of BE, as well as to other cancers a leucine-rich orphan G protein-coupled receptor, was shown to specifically label stem cells in the small intestinal and colon crypts, the so-called crypt based columnar (CBC) cells.…”
Section: Proton Pump Inhibitor Therapy and Hypergastrinemia In Bementioning
confidence: 99%